2018
DOI: 10.23938/assn.0170
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of health care professionals about end-of-life care, obstacles and ethical dilemmas in hospitals, primary care and nursing homes.

Abstract: Primary care and hospitalization presented similar results on the perception of end-of-life care, and lower results than those of nursing homes, although in these centres more ethical dilemmas and more obstacles were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Among the former, almost all of the standards are considered to be more feasible. This finding is in line with Guardia-Mancilla et al [ 45 ], whose comparative study of perceptions of end-of-life care in nursing homes, hospitals and PHC centres concluded that nursing home staff were the most optimistic in this regard. Indeed, it is logical that those providing care in nursing homes should believe it easier to achieve recommended standards since they are more aware of their own resources.…”
Section: Discussionsupporting
confidence: 89%
“…Among the former, almost all of the standards are considered to be more feasible. This finding is in line with Guardia-Mancilla et al [ 45 ], whose comparative study of perceptions of end-of-life care in nursing homes, hospitals and PHC centres concluded that nursing home staff were the most optimistic in this regard. Indeed, it is logical that those providing care in nursing homes should believe it easier to achieve recommended standards since they are more aware of their own resources.…”
Section: Discussionsupporting
confidence: 89%